A case study in forensic chemistry: The Bali bombings - Royds, D.; Lewis, Simon; Taylor, A. (Elsevier, 2005)
The Bali bombings on 12 October 2002 killed 202 people and caused international outrage. The police investigation referred to as “Operation Alliance” involved the Indonesian National Police, the Australian Federal Police and others, resulted in the arrests of key personnel and exposed the link between Jemaah Islamiah (JI) and al-Queda. This paper describes aspects of the investigation from a forensic chemists perspective. The recovery of water soluble residues from blast scenes and suspect’s residences is a challenging task that requires a meticulous and methodical approach. The concept of deploying forensic chemists and setting up a “mobile laboratory” from the outset proved to be a highly effective and efficient way to process large numbers of samples and assist investigators with relevant information at the time that it was most needed. It also identified the need for a new generation of field portable instruments.